G303(P) Child abuse in Pakistan: A qualitative study of knowledge, attitudes and practice amongst health professionals in the emergency department. (27th April 2016) - Maul, KM; Naeem, R; Khan, U; Lakhdir, M; Shah, M; Mian, A; Yousafzai, A; Brown, N
Abstract : Aims: Child abuse is a global problem and pervades all cultures and socio-economic strata. The effects of abuse can be profound and life altering for both victims and the victims' own children. There is substantial literature from High Income Countries about signs of abuse but a dearth of data from Low and Middle Income Countries like Pakistan To intervene, the first step is earlier identification. Healthcare professionals (HCPs) are ideally placed to detect abuse, but, before designing interventions to enhance services, it is necessary to understand professionals' experiences, training needs and cultural beliefs. We sought to (1) Explore the challenges that health professionals' face when managing cases of abuse; (2) Explore their cultural beliefs and to understand how these shape practise and (3) Identify their training needs. Methods: Qualitative research design using standard methodology and analysis. In-depth tape-recorded interviews were conducted in Urdu with doctors, nurses and security staff in the emergency department (ED) of a large private hospital in Pakistan. Interviews were transcribed and translated into English for thematic analysis using AtlasTi software Results: Challenges were identified at multiple levels from acknowledging to identifying to reporting abuse. HCPs offered a number of personal experiences in which they had identified abuse but considered that cases are often missed. The process of referral to legal services was poorly understood and further training and a guideline was suggested by participants. As the legal system in Pakistan does not currently allow HCPs to keep potentially abused patients in their custody, they felt restricted in their ability to act in the best interests of such children. Conclusion: HCPs have great potential for the early detection of child abuse. However, without strong social organisations, the form that their intervention should take is unclear and, even where serious cases of abuse are encountered, there are major barriers preventing the escalation of concerns. This study highlights a need to support HCPs at an institutional level through a combination of training, senior and legal support and a hospital guideline to which they can refer.